Thermal comfort assessment at parcel and logistic industry: A field study in Malaysia - Ahmad Rasdan, Ismail, Ir.; Norfadzilah, Jusoh; Mohd. Nizam, Ab Rahman, Dr.; Rozli, Zulkifli; Kumaran Kardigama (The Institution of Engineers, Malaysia (IEM), 2012)
Link to publisher's homepage at http://www.myiem.org.my/